Negotiating consent in psychotherapy - O'Neill, Patrick, 1942- (Qualitative studies in psychology., 1998)
Psychotherapists have an ethical requirement to inform clients about their treatment methods, alternative treatment options, and alternative conceptions of their problem. While accepting the basis for this "informed consent" requirement, therapists have traditionally resisted giving too much information, arguing that exposure to alternative therapies could cause confusion and distress. The raging debates over false/recovered memory syndrome and the larger move towards medical disclosure have pushed the question to the fore: how much information therapists should provide to their clients? In Negotiating Consent in Psychotherapy, Patrick O'Neill provides an in-depth study of the ways in which therapists and clients negotiate consent. Based on interviews with 100 therapists and clients in the areas of eating disorders and sexual abuse, the book explores the tangle of issues that make informed consent so difficult for therapists, including what therapists believe should be part of consent and why; how they decide when consent should be renegotiated; and how clients experience this process of negotiation and renegotiation